Dynamic Modeling of Carbon Metabolism During the Dormant Period Accurately Predicts the Changes in Frost Hardiness in Walnut Trees Juglans regia L. - Charrier, Guillaume; Lacointe, André; Améglio, Thierry (Frontiers in Plant Science, 2018)
The leafless period is often considered as inactive, although trees have to actively modulate their metabolism through the cold acclimation / deacclimation processes, to cope with frost exposure during winter and to restore growth ability in spring. Carbon metabolism is a key component of these processes through the osmotic control of extracellular ice formation and the trophic control of bud growth. The influence of temperature on the inter-conversion between starch and soluble carbohydrate has been evidenced for years, but we are currently missing an operational tool to predict starch vs. soluble carbohydrate contents during this period. For this purpose, we exposed one-year-old branches of Juglans regia to constant temperature for one to three weeks and measured the changes in carbohydrate composition at three periods (autumn, winter and spring). As expected, the temperature significantly affected the changes in carbohydrate composition, but the water content and the sampling period were also relevant. Higher starch hydrolysis was observed at low temperature (<5°C) for all sampling periods. Starch hydrolysis was also observed at warm temperature, but in autumn only. These data were used to compare three modelling approaches simulating the changes in carbohydrate composition through enzymatic analogy. The most empirical and the most mechanistic approach did not succeed to simulate external observations (Root Mean Standard Error of Prediction (RMSEP) > 30 g.g DM-1, Efficiency (Eff) < 0), whereas the intermediate model was more efficient (RMSEP = 14.67 g.g DM-1, Eff = 0.793 and 19.49, Eff = 0.103, for GFS (Glucose + Fructose + Sucrose) and starch, respectively). The accuracy of the model was further improved when using field data for calibration (RMSEP = 9.47 g.g DM-1, Eff = 0.933; RMSEP = 13.35, Eff = 0.558, for GFS and starch, respectively). This study provided an operative tool to simulate carbohydrate dynamics over leafless period that could predict frost hardiness with approx.. 3.5°C accuracy with temperature, water content and initial starch and soluble carbohydrate measurements. It should now be tested under various meteorological conditions and biological systems.